Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka - Batuwita, Sudesh; Agarwal, Ishan; Bauer, Aaron M. (Zootaxa, 2019)
A new species of Cnemaspis is described from southern Sri Lanka. Cnemaspis ingerorum sp. nov. was previously confused with C. kumarasinghei. The new species differs from C. kumarasinghei in having a lower number of ventral scales across midbody, scales on ventral sides of forelimb and hind-limb smooth (versus keeled) and dorsal caudal scales unkeeled (versus keeled). Additionally, Cnemaspis ingerorum sp. nov. has a 4.5% uncorrected ND2 sequence divergence from C. kumarasinghei and is also geographically separated from this species. Existing molecular data supports C. silvula as the sister species of the new form, however, it differs from C. silvula by the absence of keeled pectoral and abdominal scales and dorsal scales, and the absence of keeled (versus keeled) subcaudal scales.